XI Zjazd Internetowego Forum Archiwalnego (IFAR). Lublin, 9–10 XI 2017 r. - Biernat, Kamila Anna (Archiwa – Kancelarie – Zbiory, 2018)
XI Zjazd Internetowego Forum Archiwalnego (IFAR). Lublin, 9–10 XI 2017 r.